Evaluation of the strength of the norm against chemical weapons usage through the international reaction. Case study: Chemical weapons usage in Syria. - Yassin, Omnya (AUC Knowledge Fountain, 2020)
The purpose of this research is to evaluate the strength of the existing norm and conventions banning the usage of chemical weapons through the international reactions. Although it is agreed by many scholars that chemical weapons were banned due to moral, military and political reasons, this research will examine the political expediency behind the existing norm; due to the lack of efficient, strong and decisive international reactions. The paper will go through the background on Syria's chemical weapons program and will provide a brief on the Syrian civil war where the chemical weapons were used. Also, the paper will go through the chemical attacks that took place during the civil war until the accession of the Syrian regime to the chemical weapons convention and the process of the special elimination of the Syrian chemical weapons program, it will also discuss the verification and monitoring measures that were undertaken. Finally, this research will attempt to examine the different international reactions by international organizations and states, thus it would be able to draw a conclusion on the future of the norm.